In vivo imaging system (IVIS) therapeutic assessment of tyrosine kinase inhibitor-loaded gold nanocarriers for acute myeloid leukemia: a pilot study - Munteanu, Raluca-Andrada; Tigu, Adrian Bogdan; Feder, Richard; Tatar, Andra-Sorina; Gulei, Diana; Tomuleasa, Ciprian; Boca, Sanda (Frontiers in Pharmacology, 2024)
Acute myeloid leukemia (AML) is a malignancy in the myeloid lineage that is characterized by symptoms like fatigue, bleeding, infections, or anemia, and it can be fatal if untreated. In AML, mutations in tyrosine kinases (TKs) lead to enhanced tumor cell survival. The most frequent mutations in TKs are reported in Fms-like tyrosine kinase 3 (FLT3), Janus kinase 2 (JAK2), and KIT (tyrosine-protein kinase KIT), making these TKs potential targets for TK inhibitor (TKI) therapies in AML. With 30% of the mutations in TKs, mutated FLT3 is associated with poor overall survival and an increased chance of resistance to therapy. FLT3 inhibitors are used in FLT3-mutant AML, and the combination with hypomethylating agents displayed promising results. Midostaurin (MDS) is the first targeted therapy in FLT3-mutant AML, and its combination with chemotherapy showed good results. However, chemotherapies induce several side effects, and an alternative to chemotherapy might be the use of nanoparticles for better drug delivery, improved bioavailability, reduced drug resistance and induced toxicity. The herein study presents MDS-loaded gold nanoparticles and compares its efficacy with MDS alone, on both in vitro and in vivo models, using the FLT3-ITD-mutated AML cell line MV-4-11 Luc2 transfected to express luciferin. Our preclinical study suggests that MDS-loaded nanoparticles have a better tumor inhibitory effect than free drugs on in vivo models by controlling tumor growth in the first half of the treatment, while in the second part of the therapy, the tumor size was comparable to the cohort that was treatment-free.